China’s Pragmatic Appropriation of Global South Narrative - Fachrurreza, Ahmad Mujaddid; Ningsih, Sabda; Yunazwardi, Muhammad Iqbal (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2026)
The revival of Global South studies in International Relations signifies a major transformation in contemporary global dynamics. This article addresses the question of how China appropriates the Global South narrative and how this shift reflects both coloniality of power and heterarchy of power. Using a discourse analysis approach, the study examines official speeches, policy documents, and global initiatives such as the Belt and Road Initiative (BRI), BRICS, and the G77+China. The findings demonstrate that China employs South-South solidarity rhetoric to position itself as the leader of the Global South, yet in practice reproduces coloniality by creating new forms of dependency. Furthermore, the contemporary Global South reveals a heterarchical structure, where emerging powers such as China dominate smaller states. This indicates a shift in the meaning of the Global South: from the Bandung Spirit’s emancipatory ethos of anti-imperialism toward a pragmatic economic-political bloc driven by national interests. Thus, the revival of the Global South is paradoxical: it offers new opportunities for multipolarity among developing countries, while simultaneously undermining the emancipatory ideals of solidarity and equality that once defined the Bandung Spirit. Keywords: Global South; Bandung Spirit; China; Coloniality of Power; Heterarchy of Power Kebangkitan kembali kajian Global South dalam studi Hubungan Internasional menandai transformasi penting dalam dinamika global kontemporer. Artikel ini berangkat dari pertanyaan mengenai bagaimana China mengapropriasi wacana Global South dan bagaimana pergeseran makna ini mencerminkan kolonialitas dan heterarki kuasa. Dengan menggunakan metode analisis wacana, penelitian ini menelaah pidato resmi, dokumen kebijakan, serta inisiatif global seperti Belt and Road Initiative (BRI), BRICS, dan G77+China. Temuan pada penelitian menunjukkan bahwa China menggunakan retorika solidaritas selatan untuk memosisikan dirinya sebagai pemimpin Global South, namun praktiknya mereproduksi logika kolonialitas dengan menciptakan relasi ketergantungan baru. Selain itu, Global South kontemporer memperlihatkan struktur heterarki emerging powers seperti China menempati posisi dominan atas negara-negara kecil. Hal ini mengindikasikan adanya pergeseran makna Global South: dari spirit emansipatoris Bandung yang menolak imperialisme, menuju blok ekonomi-politik pragmatis yang sarat kepentingan nasional China. Dengan demikian, kebangkitan Global South bersifat paradoksal: membuka ruang multipolaritas baru bagi negara-negara berkembang, tetapi sekaligus mengikis nilai-nilai emansipasi dan kesetaraan yang menjadi fondasi Bandung Spirit. Kata-kata Kunci: Global South; Bandung Spirit; China; Kolonialitas Kekuasaan; Heterarki Kekuasaan